Hydrogen Sulfide Alleviates Acute Myocardial Ischemia Injury by Modulating Autophagy and Inflammation Response under Oxidative Stress. (1st August 2018) - Bai, Ya-dan; Yang, Yu-rong; Mu, Xue-pan; Lin, Ge; Wang, You-ping; Jin, Sheng; Chen, Ying; Wang, Ming-jie; Zhu, Yi-chun
Abstract : This study aims to investigate the influence of excessive oxidative stress on cardiac injury during acute myocardial ischemia (AMI), with a focus on apoptosis, autophagy, and inflammatory cell infiltration, and to detect the role of hydrogen sulfide (H2 S) in this process. We found that SOD1 knockout (KO) mice showed excessive oxidative stress and exacerbated myocardium injury after AMI. Increased apoptosis and inflammation response in the ischemic myocardium contribute to this deterioration, whereas enhanced autophagy plays a protective role. Myocardial inflammation after AMI was much more severe in SOD1 KO mice than in wild-type mice. Pretreatment with the H2 S donor NaHS reduced autophagy and apoptosis levels in the ischemic myocardium and alleviated the regional inflammation response in the cardiac tissues of SOD1 KO mice. Moreover, autophagy and apoptosis levels were significantly enhanced in SOD1 knockdown primary neonatal rat cardiomyocytes (NRCMs) under glucose deprivation. Pretreatment with NaHS can partially inhibit this elevation. Taken together, we found that excessive oxidative stress can aggravate cardiac injury during AMI. Exogenous H2 S can alleviate cardiac injury during AMI by reducing apoptosis and inflammation response in heart tissues under oxidative stress.